FUNCTIONAL DYNAMICS OF THE SHOW IN MODERN MEDIA: TRAVEL SERIES` STYLISTIC NATURE - Dmytro Dergach (Езиков свят)
The paper examines the current trend towards reorientation of the informational context of the mass media. The author's argumentation is grounded on an analysis of communicative processes, wherein analytical, entertaining, and cognitive segments of media discourse are effectively realized in appropriate content. Consequently, this approach enhances the functional status and potential of literary language within this area. The following interpretation focuses on the show as a genre of media communication that relies on an effective combination of verbal and audiovisual means. These components are employed to facilitate a multifunctional, creolized presentation of meticulously prepared and thoughtfully structured content within the media space. Furthermore, the author emphasizes the show's entertaining, cognitive, and communicative functions, particularly its role in shaping the language consciousness of the mass audience through informational and emotional influence. The show media genre effectively illustrates the tendency towards functional syncretism of forms of mass communication. For the first time in current linguistics, the plural form – genres of the show – is used to facilitate a media linguistic analysis of the show's multifunctional nature. Additionally, invariants that are synchronized with their functions in the genre core are identified. Among relevant communication invariants of the show genre (talk show, talent show, intellect show, cooking show, etc.) the travel show is one of the most representative for stylistic investigation of mass media functional dynamics. Its communicative nature is the object of media linguistic interpretation in the article.